2008
DOI: 10.1002/art.23523
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ankylosing spondylitis on work and family life: Comparisons with the US population

Abstract: Objective. To examine the impact of ankylosing spondylitis (AS) on work disability, nonparticipation in the labor force, marriage, divorce, and childbearing. Methods. In this cross-sectional survey, we asked AS patients (n ‫؍‬ 591, 72.8% men, mean age 48.9 years) from the Los Angeles, Houston, San Francisco, and Washington, DC metropolitan areas about work and family life. The proportion of patients who were work disabled, did not participate in the labor force, had never been married, were divorced, or had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 21 publications
5
43
1
2
Order By: Relevance
“…In the present study, patients with JoAS showed significantly lower rates of getting married (P = 0.013) compared with patients with AoAS. The good news may be that only 1 patient in all of the 139 participants experienced divorce, which is inconsistent with a previous report (27). This might be partly related to the traditional Chinese approach towards marriage and family.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…In the present study, patients with JoAS showed significantly lower rates of getting married (P = 0.013) compared with patients with AoAS. The good news may be that only 1 patient in all of the 139 participants experienced divorce, which is inconsistent with a previous report (27). This might be partly related to the traditional Chinese approach towards marriage and family.…”
Section: Discussioncontrasting
confidence: 59%
“…Marriage is no doubt an important part of life. Nevertheless, it is reported that AS patients may have low marriage rates and high rates of divorce (27). Patients with JoAS, however, may be facing an even worse marital situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EASIC study was performed in 6 Western European countries. As mentioned previously, the magnitudes of productivity loss vary across countries (3)(4)(5)44,45). This variation may be attributed to the differences in organization of the social security system, to the levels of support for persons with a chronic disease, and probably to work culture (5).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the population studied, its prevalence varies between 0.5% and 1% in white populations 1 . Most frequently presenting in early adulthood, AS can lead to substantial functional limitation in people of working age 2 . As such it presents a significant burden of morbidity and health care expenditure 3 .…”
mentioning
confidence: 99%